Peran Mahasiswa Dalam Mensosialisasikan Protokol Kesehatan Covid-19 Melalui Program KKL DR IAIN Padangsidimpuan - Pulungan, Mhd Syukri (Jurnal at-Taghyir, 2020)
The objectives of this study are: (1) to study the form of Field Work Lecture Program from thePadangsidimpuan State Islamic House of Religion (2) to study the role of students in socializing the COVID-19 health protocol in the KKL program from home State Islamic Institute Padangsidimpuan in 2020. This research was conducted in 10 villages / kelurahan which became the location of the KKL DR participants that took place from June 2020 to August 2020. The determination of the informants was carried out by purposive sampling, namely the technique of collecting informants who deliberately involved 25 people and the research data was obtained through the creation of a questionnaire distributed using the goggle form . as for the descriptive qualitative analysis. The results of the research show that research (1) in the form of Field Work Lectures from Home quotes the delivery of information related to the COVID-19 Health Protocol by using various online and offline media such as: Facebook, Twitter, Instagram, Youtube and Blog which provide posters and leaflets with displays. (2) the role of students in disseminating the health protocol COVID-19 is quite effective because students are included in the group category (in groups) and are more effective in providing information to the public.